2014
DOI: 10.4028/www.scientific.net/amm.638-640.2097
|View full text |Cite
|
Sign up to set email alerts
|

Study of Distribution and Quantification of Flammable Gas in Confined Space

Abstract: The contribution deals with leakage of natural gas from domestic low-pressure piping. Spreading of the leaked natural gas in the confined space is deals with and the areas are defined where local hazardous concentrations are formed. Mathematical CFD models provide broad overview of spreading of natural gas, in dependence on the elapsed time from the start of leakage. The contribution should improve the understanding of spreading and distribution of mixture of gaseous fuels in confined spaces, and thus leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…The results showed that different hazardous areas were formed after the gas leaked out and diffused at different locations. Tulach et al 23 used CFD models to investigate the way (velocities and directions) of distribution of natural gas leaking out of predefined leakage to the confined space, and the areas were defined where local hazardous concentrations were formed. The results improved the understanding of the spreading and distribution of a mixture of gaseous fuels in confined spaces.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that different hazardous areas were formed after the gas leaked out and diffused at different locations. Tulach et al 23 used CFD models to investigate the way (velocities and directions) of distribution of natural gas leaking out of predefined leakage to the confined space, and the areas were defined where local hazardous concentrations were formed. The results improved the understanding of the spreading and distribution of a mixture of gaseous fuels in confined spaces.…”
Section: Introductionmentioning
confidence: 99%